Build Mobile Apps with Ionic 4 and Firebase Hybrid Mobile App Development - Cheng, Fu (Apress, 2018)
Leverage your existing web development skills to learn the whole cycle of hybrid mobile app development. This edition is fully updated with the changes in Ionic 4, including Stencil, a new framework based on the web components standard. It explains Ionic and Firebase in detail, including how to create hybrid mobile apps using using React and Vue, and run those apps in an internal browser using a wrapper created by Apache Cordova. Build Mobile Apps with Ionic 4 and Firebase shows you how to focus on developing front-end code, without needing to manage any back-end code or servers. You'll learn in the context of building a Hacker News client app, which can view top stories in Hacker News, view comments of a story, and add stories to favorites. Explore how Ionic 4 uses Angular as the JavaScript framework to easily develop apps using an interface similar to native apps, and how to access Firebase, a real-time database, in web apps using JavaScript.